863 Understanding the profile of injuries for vulnerable road users: a data linkage study. (1st September 2016) - Watson, Angela; Blackman, Ross; Vallmuur, Kirsten; Watson, Barry
Abstract : Background: Unless substantial gains are made in the prevention of road crashes, they will become the third ranked global burden of disease and injury by 2020. A growing proportion of this burden relates to vulnerable road users (e.g., motorcyclists, cyclists, and pedestrians). In order to reduce this burden, there is a need to fully understand the nature and contributing circumstances of crashes and the resulting injuries. While police-reported crash data contain detailed information about crash circumstances, they lack accurate information about the severity and nature of injuries which are included in hospital data. By bringing these data collections together using data linkage, the relationship between the characteristics of vulnerable road user crashes and their resulting injuries were explored. Methods: Data from the Queensland Road Crash Database (QRCD) and the Queensland Hospital Admitted Patients Data Collection (QHAPDC) for the year 2010 were linked. There were 1, 382 police-reported motorcyclist injuries that linked to a hospital record (42% of all police-reported motorcyclist injuries), 429 cyclists (25%), and 644 (39%) pedestrians. The relationships between crash characteristics such as counterpart involvement, alcohol, fatigue, speed, and helmet use and injury severity (e.g., ICD-derived Injury Severity Score ICISS, length of stay), nature, and body region were examined. Results: The involvement of motor vehicles was related to more severe injury outcomes for vulnerable road users (between 1.5 and 2.8 times the odds of being serious), as were high speeds (between 1.2 and 1.6 times), alcohol (2.1 times for motorcycles), and helmet non-use (between 1.9 and 2 times). The circumstances of crashes, such as counterpart type and crash location, influenced injury nature and body region. Conclusions: By bringing together circumstance data from police and injury outcome data from hospitals, a greater understanding of the link between crash circumstances and injury outcomes was achieved. Studies using linked data can better inform intervention and treatment for a more holistic approach to the reduction of road trauma for vulnerable road users.